JavaScript mastery from zero to hero : prepare for coding interviews. (Packt Publishing, 2023)
We understand that learning programming can be overwhelming, especially when it comes to problem-solving under pressure during coding interviews. That's why we have developed an efficient model of hours upon hours of practice examples, complete with multiple solutions and a glossary of definitions. This approach allows you to move through the course at your own pace, starting with the very basics of programming in JavaScript, such as datatypes, or diving right into code examples, matrices, Fibonacci sequences, and more. The course is divided into four main sections. First, an introduction will help you set up the necessary tools and provide an overview of what you can expect to learn. From there, the course covers the introduction to programming and JavaScript basics for absolute beginners. Next, you will explore data structures, from zero to intermediate level, before moving on to the fundamentals of algorithms. Finally, you will learn about advanced algorithms and data structures, giving you a complete picture of this essential skill set. You will gain the experience and focused practice needed to overcome any challenge in JavaScript and programming data structures and algorithms. By the end of the course, you will be confident in your knowledge and prepared to tackle coding interviews, impressing your future interviewer and colleagues alike. What You Will Learn Sign in to the CodeSandbox IDE and create a new Vanilla.js template on it Look at the comments, datatypes, variables, functions, and operators in JavaScript Use the splice method to decode the puzzle and update new user database Build an Uber app customer JavaScript object database Automate a company's website with correct formatting in JavaScript Understand the Fibonacci series and recursion in JavaScript Audience This course is designed for individuals who want to gain a comprehensive understanding of JavaScript and tackle coding interview challenges with confidence. If you have been struggling to grasp the fundamentals of programming or feel uncertain about solving coding problems, this course is perfect for you. If you are interested in pursuing a career as a programmer or seeking to upskill in advanced topics, whether you are a beginner or have prior experience with JavaScript, this course will teach you advanced concepts in data structures and algorithms to take your skills to the next level. No programming experience is required as you will learn everything from the ground up. About The Author Clarian North: Clarian North is a recognized industry-certified instructor, CEO of Orbital LLC, and a senior project engineer with over 90K enrolments worldwide. His students have gone on to work for some of the biggest production companies such as Universal, Google, Amazon, Warner, and the BBC. He has contributed to viral streams, grown a unique digital imprint in over 80 countries, and been featured in Rolling Stone, Billboard, Guardian, Bloomberg, and Vice. He has worked for majors, indies, and international publishing houses, including Grammy-nominated and award-winning productions, mixing for Emirates Airline Inflight Radio, and producing for Kompakt Records. He is dedicated to giving accessible and comprehensive tech courses, teaching complex subject matter with clear and example-based explanations, and guiding students through complex techniques with just a computer and free software.